Clinical, Etiological and Antibiotic Susceptibility Profiles of Community-Acquired Urinary Tract Infection in a Western Hemisphere of Baghdad - Hussein, Naser S (Bangladesh Journal of Medical Science, 2015)
Background: In majority of community-acquired urinary tract infection (CA-UTI) cases, physicians can prescribe empirical therapy without a pretreatment urine culture especially in resource poor settings, where the cost of urine culture is more than cost of treatment itself. Objective: With growing problem of drug resistance globally as well as data on CA-UTI in Iraq are scare. We conduct this study to analyze clinical presentation, etiology and antibiotic sensitivity of bacteria causing community acquired urinary tract infection (CA-UTI). Material and Methods: Outpatients urine cultures and clinical presentations were collected from April 2012 to October 2012. A positive urine culture was defined as growth of a single bacteria with colony count of more than 100,000 CFU/ml and disk diffusion technique was performed to determine antibiotics susceptibility of isolated bacteria species. Clinical symptoms, causative uropathogens and their antibiotic sensitivity were recorded. Results: Of 299 urine cultures processed, a positive urine culture was detected in 100 subjects. Dysuria and bladder irritability (frequency and urgency) were the most common clinical presentation. 39% of isolated bacteria was Escherichia coli and Staphylococcus strains (30%). The isolated uropathogens showed a substantial sensitivity reduction to most of test antibiotics. Conclusion: Clinical presentation had a minor role in diagnosis of CA-UTI and this study revealed that E. coli and Staphylococcus strains were most prevalent isolated uropathogens. Susceptibility test showed there was a high sensitivity to nitrofurantoin, amikacin and imipenem. Bangladesh Journal of Medical Science Vol.14(4) 2015 p.352-358